The skip's guide to bowls - Mills, Chris, 1948- (London : A. & C. Black, 1993)
Analyzes the duties and necessary qualities of skips and explains how the best skips make the most of every situation. Topics covered include bowls etiquette, picking team members for pairs, triples and fours matches, how to handle different personalities and assessing opposing players.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid
Keywords: Lawn bowls; Bowls (Game); Bowls (Ball games)